OPTIMIZATION ANALYSIS OF THE SCROLL EXPANDER SPECIAL TOP PROFILE CORRECTION IN THE INLET PORT - JIA JianPing; LI YuFeng; LIU GuoPing; ZHANG GuoLin; LI Bin (Jixie qiangdu)
The study has been done with focus on the pneumatic power conversion efficiency by analyzing Perfect Meshing Profile（ PMP） correction of the scroll expander with the serious top profile invasion of the inlet port problem in application. The maximal invasion rate reaches 50%,which leads to the increase of inlet air flow friction coefficient. Therefore,on the basis of the circular arc plus line-shaped top profile correction,special correction method for the top profile was proposed. According to the feature of special top profile correction method,it comes to a conclusion that special top profile correction has low invasion rate（ the maximum only was 9%） and airflow friction coefficient of the inlet port decreases. In addition,in the intake process,at any time the actual inlet port can remain relatively smoothly,therefore reducing the airstream friction coefficient and the inlet port power loss. And what’s more,symmetric synchronous inflation of scroll expander has been accomplished,and consequently the results are smooth power delivery with reducing the mechanical vibration. Theoretically,the scroll expander pneumatic power conversion efficiency has been improved by reducing inlet port inflation power loss.